The Feasibility of STAD Model Learning Devices Assisted by Flipbooks on Materials Structure and Function of Plants for Class VIII - Dita Ariani; Kurnia Ningsih; Afandi Afandi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
This study aims to determine the validity and reliability of the development of learning tools using the STAD model assisted by flipbooks. This study uses the Borg & Gall development model with the following stages: potential and problems, data collection, product design, design validation, and design revision. The validation of the learning device was measured using a validation sheet. The data obtained were analyzed using the Aiken's V formula with a minimum value of 0.78 for 6 validators. The results of the validation of learning devices were declared valid with the average acquisition of Aiken's V calculations in the lesson plan of 0.91, flipbook media of 0.88, LKPD of 0.88, and evaluation questions of 0.90. The reliability of the learning device was tested using the ICC (Interclass Correlation Coeficient) test with SPSS Version 25 software, the results obtained from the reliability of the lesson plan of 0.778 included in the good category, while the reliability value for flipbook media obtained results of 0.537, LKPD of 0.565, and evaluation questions of 0.626 is included in the medium category. It is hoped that this learning device can be tested by the next researcher.